2020
DOI: 10.1098/rsta.2018.0429
|View full text |Cite
|
Sign up to set email alerts
|

Habitability of the marine serpentinite subsurface: a case study of the Lost City hydrothermal field

Abstract: The Lost City hydrothermal field is a dramatic example of the biological potential of serpentinization. Microbial life is prevalent throughout the Lost City chimneys, powered by the hydrogen gas and organic molecules produced by serpentinization and its associated geochemical reactions. Microbial life in the serpentinite subsurface below the Lost City chimneys, however, is unlikely to be as dense or active. The marine serpentinite subsurface poses serious challenges for microbial activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 111 publications
(200 reference statements)
1
65
0
Order By: Relevance
“…Additionally, H 2 , CO and NH 3 found to be abundant in the deep metamorphic fluids in this study might fuel widespread chemolithoautotrophy as recently reported at convergent margins 2,3 and other subsurface continental settings 87 . Heterotrophic and fermentative members of the community commonly reported in other continental settings 78,87 may be supported by the aqueous organic species resulting from abiotic synthesis (e.g., formate and acetate 88 ). Overall, the presence of a large supply of reduced volatile species has the potential to support diverse microbial assemblages at convergent margin.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, H 2 , CO and NH 3 found to be abundant in the deep metamorphic fluids in this study might fuel widespread chemolithoautotrophy as recently reported at convergent margins 2,3 and other subsurface continental settings 87 . Heterotrophic and fermentative members of the community commonly reported in other continental settings 78,87 may be supported by the aqueous organic species resulting from abiotic synthesis (e.g., formate and acetate 88 ). Overall, the presence of a large supply of reduced volatile species has the potential to support diverse microbial assemblages at convergent margin.…”
Section: Discussionmentioning
confidence: 88%
“…Serpentinite-hosted systems are of astrobiological interest because they provide a source of energy for life that does not require sunlight or vigorous magmatic activity (1). These systems are thought to be present on icy worlds such as Jupiter's moon Europa and Saturn's moon Enceladus (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Modern serpentinising systems harbour temperature, pH and redox gradients [94] and provide carbon (mostly in the form of CO 2 /carbonates), sulphur (H 2 S and sulphide minerals), and in lesser or trace amounts also nitrogen and phosphate [137]. A unique feature of serpentinising systems is the continuous production of hydrogen (H 2 ) from water, providing the surroundings with a constant supply of electrons, a very low midpoint potential [138], and a chemical energy source [139–141].…”
Section: Serpentinising Systems and Water Activitymentioning
confidence: 99%